On International Legal Guarantees for Ensuring Personal Rights and Freedoms in the Subjects of the Russian Federation - G. G. Boskhomdzhieva (Московский журнал международного права, 2008)
The article “On International Legal Guarantees for Ensuring Personal Rights and Freedoms in the Subjects of the Russian Federation” deals with the present system of human rights guarantees: international and domestic ones (that of the Russian Federation) and also guarantees constituted on the Russian regional level. By analogy with the Federal Constitution, constitutions (charters) of most constituent territories of the Russian Federation declare of their recognition of international standards as an inseparable part of their legal system. International law lays special emphasis on personal and political rights guarantees. The author concludes that one of the main objectives of the Russian federative state is to provide unified standards for human rights pursuance and protection on the whole of its territory – in all its constituent territories.